Development of Canva-Based Digital Teaching Materials to Train Students' Understanding of Dynamic Fluid Concepts - Endasyari Juliarti (Indonesian Journal of E-learning and Multimedia (IJOEM), 2022)
The research aims to analyze students' needs for Canva-based digital teaching materials on dynamic fluid material. Research is a type of research and development. The design of the development model uses the ADDIE steps (Analysis, Design, Develop, Implementation, Evaluation). However, this article will only discuss the results at the analysis stage. What was done at the analysis stage was distributing questionnaires to find out students' needs for Canva-based digital teaching materials. The sample in this study were students of class XI IPA at SMAN 4, SMAN 5, and SMAN 7 Bengkulu City. Data collection techniques used include non-test techniques. Data analysis techniques using qualitative and quantitative data analysis techniques. The results of the study show that students need electronic teaching materials (E-Modules) that can train their ability to understand concepts in dynamic fluid materials.